Assess Restricted Pulmonary Function in Chronic Hepatitis C Patients at Various Phases - Faisal Rahman, Zainab Rizwan, Huma Hameed, Sohail Hussain, Muhammad Saqib Habib, Talal Safdar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chronic hepatitis C infection has both hepatic and extra-hepatic symptoms, both of which are influenced by the inflammatory response triggered by HCV. Chronic HCV induces inflammation that manifests itself in the liver and beyond. Persistent HCV infection may be associated with reduced pulmonary functions especially in patients with high viremia levels. Objective: The objective of study was to examine restricted pulmonary function in chronic hepatitis C patients during different phases. Study Design: Cross-sectional study Place and Duration: Department of Medicine Social Security Teaching Hospital Ferozepure Road Lahore. From 01.02.2022 to 30.08.2022. Methods: There were 94 cases of chronic hepatitis included in this study. After gaining the participants' informed consent, we documented their age, sex, BMI, and smoking status in detail. Patients underwent for abdominal ultrasound. The anti-HCV antibody test was run with a third-generation ELISA (Ortho HCV ELISA) kit using 3 ml of blood and pulmonary function test were performed to eavaluate restrictive lung disease. Data was entered and analyzed in SPSS 24.0 and presented as frequency and percentages. Results: Among 94 cases, 57 (60.6%) were males and 37 (39.4%) were females. Mean age of the patients was 46.9±4.53 years and mean BMI was 25.4±6.29 kg/m2. Majority of the cases 51 (54.3%) had rural residency. There were 64 (68.1%) cases had smoking history. We found that 17 (18.1%) cases had severe HCV, 45 (47.9%) cases had moderate and 32 (34.04%) patients had mild HCV. There were 37 (39.4%) cases had restrictive pulmonary function among all cases. Among 37 cases of pulmonary disease, majority had severe HCV infection. Conclusion: We concluded in this study that the patient with HCV infection had higher incidence of restrictive pulmonary disease. Majority of the patients were males and had smoking history. Severe cases of HCV mostly had restrictive disease. Keywords: HCV, Restrictive Pulmonary Disease, Males, Smoking